Revisiting the Make-or-Buy Decision: Conveying Information by Outsourcing to Rivals - Arya, Anil; Mittendorf, Brian; Yoon, Dae-Hee (The Accounting Review, 2014)
ABSTRACT The textbook make-or-buy decision is typically described as choosing the cheaper of the two sourcing options. However, research in accounting has consistently demonstrated that strategic and informational considerations often complicate such seemingly straightforward criteria. In a similar vein, this paper shows that when a firm becomes privy to accounting information pertaining to its profitability, its sourcing choice has powerful informational reverberations. This is because input procurement from an outsider serves to convey both profitability information and strategic positioning. Conveying profitability information refers to the fact that the size of the input order provides the supplier a credible signal of the firm's internal accounting information and, thus, its relative ability to compete in the marketplace. Conveying strategic positioning refers to the fact that the upfront placement of the input order also informs the supplier about the firm's chosen strategic choices in the marketplace. We demonstrate that both sources of information conveyance together can point to a firm preferring to buy inputs from a retail rival even when it can make them internally at a lower cost. This penchant for outsourcing to a rival is more pronounced the more accurate the firm's accounting system.